2019
DOI: 10.1111/1747-0080.12583
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality is more strongly related to food skills rather than cooking skills confidence: Results from a national cross‐sectional survey

Abstract: Aim: While diet quality has declined globally, the promotion of cooking skills as a potential target to counter the decline has been proposed. The aim of the current study was to investigate the relationship between food and cooking skills and diet quality in Australian adults. Methods: A sample of 910 Australian adults completed an online cross-sectional survey to evaluate their level of cooking and food skills confidence, food related psychological variables, diet quality using the Australian Recommended Foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
76
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 39 publications
(63 reference statements)
8
76
2
1
Order By: Relevance
“…The cooking confidence and creativity scales included in this questionnaire were based on the cooking identity and food creativity scales used in a previously validated questionnaire [23], with minor modifications. The cooking identity scale was used as a measure of cooking confidence, as it contains items such as "others view me as a good cook".…”
Section: Cooking Confidence Scores and Cooking Creativity Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…The cooking confidence and creativity scales included in this questionnaire were based on the cooking identity and food creativity scales used in a previously validated questionnaire [23], with minor modifications. The cooking identity scale was used as a measure of cooking confidence, as it contains items such as "others view me as a good cook".…”
Section: Cooking Confidence Scores and Cooking Creativity Scoresmentioning
confidence: 99%
“…When individuals lack cooking skills, they become susceptible to messages about ease of preparation and taste [22]. As such, the use of convenience and processed food has increased, reducing the need for cooking skills [23]. The term "convenience cooking product" refers to products that provide a base for cooking meals that lowers the cooking time and preparation time.…”
Section: Introductionmentioning
confidence: 99%
“…The null results regarding mechanical skills may suggest that more complex food skills are needed to have an impact on diet quality. 20 Counter to the hypothesis, selfconfidence in mechanical techniques and conceptualizing food was positively associated with both avoidable and unavoidable food waste. Estimates of avoidable food waste per unit increase in confidence of mechanical techniques ranged from 8.3 to 70.1 g, which on the upper end is equivalent to approximately half of an apple being wasted each day.…”
Section: Discussionmentioning
confidence: 99%
“…Several other papers present research across diverse areas of practice. In a large cross‐sectional study reported by Lavelle et al we learn that diet quality is more strongly related to food skills rather than cooking skills confidence. Original research investigating different aspects of renal function and management are included, as is the SPICE trial protocol …”
mentioning
confidence: 84%